Peningkatan Kualitas Produk dengan Metode Six Sigma dan Kaizen - Mochammad Basjir; Suhartini; Nur Robbi (Jurnal Serambi Engineering, 2024)
The company has a strategy to ensure its survival and increase its competitiveness. PT. XYZ is a foreign company that operates in the industrial manufacturing aspect. The products manufactured are lamp cases, lamp holders, front grills, port rings, screw hole covers and air conditioning boxes. PT. XYZ also produces supporting components, one of which is cup buses. The problem in the research is that bus cup products often experience defective products with a percentage of 30% - 40%. This research aims to identify the causes of defects in bus cup products, determine the most dominant types of defects in bus cup products, and determine proposed corrective actions for bus cup products at PT. XYZ. The research will use Six Sigma and Kaizen methods. The research results show that there are 4 (four) types of Critical to Quality, namely Short Mold, Shink Mark, Warping and Black Dot, while the DPMO is 131,723 and produces a Sigma of 42.37. This study suggests improvements: the production manager checks every 1 hour, the operator continuously checks the materials and the injection machine. Control of work activities, regular maintenance of machines, care of raw materials and environmental conditions of the production area.